The day I became indigenous – the ontological identification with the other as decolonizing metamorphosis - Taddei, Renzo (Revista do Instituto de Estudos Brasileiros, 2018)
This text combines reflections on the challenges encountered by me in my ethnographic work with the Cacique Cobra Coral Foundation, in special in what concerns the transformation in the way alterity was experienced throughout the ethnographic process, with criticisms made by indigenous anthropologists to anthropology and its practices, with the goal of making elements of the ethnographic research illuminate, as much as possible, uncomprehended dimensions of the mentioned criticisms. The text then offers some ref lections on the impacts of the appearance of the whole contingent of sel f-declared “animi st ” anthropologists, in a context in which anthropology tacitly reproduces, in some of its practices, the materialistic naturalism of the so called “hard” sciences.